A deep dive into the development of sea squirts - Satoh, Noriyuki (Nature (London), 2019)
An analysis of gene expression in sea-squirt embryos at different stages of development deepens our understanding of how the body plans of vertebrates might have evolved from those of less complex animals. Sea-squirt larvae provide clues about the evolution of vertebrates.